Introduction to practical fluid flow - King, R. P. (Oxford ; Boston : Butterworth-Heinemann, 2002)
Introduction to Practical Fluid Flow provides essential information on the the solution of practical fluid flow and fluid transportation problems through the application of fluid dynamics. Emphasising the solution of practical operating and design problems using the latest methods, the text concentrates on computer-based methods throughout, in keeping with modern trends in engineering. With a focus on the flow of slurries and non-Newtonian fluids, it will be useful for and engineering students who have to deal with practical fluid flow problems. The book is supported by an accompanying CD ROM which provides a toolbox of computer methods. These enable readers to use all of the problem solving methods shown in the book's illustrated examples. Emphasises flow of slurries and Non-Newtonian fluids. Covers the application of fluid dynamics to the solution of practical fluid flow and fluid transportation problems.
Preface; Introduction; Flow of fluids in piping systems; Interaction between fluids and particles; Transportation of slurries; Non-newtonian slurries; Sedimentation and thickening; Index.
Includes bibliographical references and index.
Keywords: Fluid dynamics; Electronic books